Given, "(y-xz)p+(x+yz)q = x^{2}+y^{2}".
This equation is of the form "Pp+Qq=R" (Lagrange's linear partial differential equation).
Here, "P = y-xz, Q=(x+yz), R = x^{2}+y^{2}".
The subsidiary equations are
"\\dfrac{dx}{P}=\\dfrac{dy}{Q}=\\dfrac{dz}{R}\\\\\n\\dfrac{dx}{y-xz}=\\dfrac{dy}{(x+yz)}=\\dfrac{dz}{x^{2}+y^{2}}~~~~~~~~~~~-(1)".
Using the method of multipliers in each fraction,
"\\dfrac{ydx}{y(y-xz)}=\\dfrac{xdy}{x(x+yz)}=\\dfrac{-dz}{-1(x^{2}+y^{2})}"
="\\dfrac{ydx+xdy-dz}{y(y-xz)+x(x+yz)-(x^2+y^2)}"
="\\dfrac{ydx+xdy-dz}{y^2-yxz+x^2+xyz-x^2-y^2}"
="\\dfrac{ydx+xdy-dz}{0}"
"\\to ydx+xdy-dz=0"
"\\to d(xy)=dz"
Integrating Both the sides
"\\int d(xy)=\\int dz"
"xy=z+c" "_1"
c"_1" =xy-z
Again using method of multiplier
="\\dfrac{xdx}{x(y-xz)}=\\dfrac{-ydy}{-y(x+yz)}=\\dfrac{zdz}{z(x^{2}+y^{2})}"
="\\dfrac{xdx-ydy+zdz}{xy-x^2z-yx-y^2z+zx^2+zy^2}"
"= \\dfrac{xdx-ydy+zdz}{0}"
"\\to xdx-ydy+zdz=0"
Integrating above equation we get,
"\\to \\dfrac{x^2}{2}-\\dfrac{y^2}{2}+\\dfrac{z^2}{2}+c=0"
"\\to c_2=y^2-x^2-z^2"
The solution of the given equation are
"xy-z=c_1" and "x^2-y^2+z^2+c_2=0"
Comments
Leave a comment